Small Watershed Management and Eco-rehabilitation on the Loess Plateau of China - Liu, Guobin; Tian, Junliang; Chen, Yumin; Liu, Puling (MTT, 2005)
The Loess Plateau is well known for its deep loess deposits and serious soil erosion. This paper analyses the characteristic of soil erosion on the Plateau and reviews the small watershed management and ecosystem rehabilitation practice and development in the future. In the last 30 years, the government has paid great attention on the integrated small watershed management and restoration of the Loess Plateau. Based on the theory and practice, Chinese scientist presented 28 words strategy and conservational eco-agriculture, developed the integrated health assessment indicators on the Plateau. The further research on small watershed management and ecosystem rehabilitation such as to combine the slope cropland converting with engineering practice, strength on the ecosystem natural rehabilitation and enlarge the management to the medium scale as well as environment effect assessment on conservation practice were suggested.
Keywords: Ys; Loess Plateau; small watershed; integrated management; ecorehabilitation